2022
DOI: 10.3390/jcm11237156
|View full text |Cite
|
Sign up to set email alerts
|

Local Resection in Choroidal Melanoma: A Review

Abstract: Surgical resection is widely used to treat small tumours located in the iris and the ciliary body, due to the accessibility of these sites. By contrast, surgical removal of choroidal tumours is substantially more challenging, which is why this procedure is performed only at specialised centres. In the present article, we review the literature on surgical resection of choroidal tumours, which can be performed as endoresection (ab interno) or transscleral resection (ab externo). An important aim of this review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Reported rates of long-term local recurrence and enucleation after endoresection for UM are quite variable, ranging from 0% to as high as 23% [17]. Damato In our series, only one patient developed liver metastases and died as a consequence.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Reported rates of long-term local recurrence and enucleation after endoresection for UM are quite variable, ranging from 0% to as high as 23% [17]. Damato In our series, only one patient developed liver metastases and died as a consequence.…”
Section: Discussionmentioning
confidence: 58%
“…It can be performed through a trans-scleral approach (exoresection) or through an internal approach utilizing pars plana vitrectomy (endoresection). Endoresection surgery has been utilized over the last three decades with promising results, but only the advances in vitreoretinal surgery technology made in recent years have signi cantly improved the technique [16,17]. In recent years, endoresection of the tumor utilizing pars plana vitrectomy combined with adjuvant ruthenium brachytherapy has proven to be an effective treatment for selected patients with large choroidal melanoma [12,17,31].…”
mentioning
confidence: 99%
“…Radiotherapy can be administered in the form of brachytherapy, used as first choice treatment for smaller tumors, or proton beam radiotherapy and stereotactic radiosurgery, which are preferably used in medium and large tumors [3,6]. The surgical resection of the tumor is another viable option for selected patients with UM [7][8][9][10][11][12][13][14][15][16][17]. In consideration of the multiple treatment options currently available, treatment should be highly individualized depending on several factors related to the tumor itself, such as dimensions, location, involvement of the surrounding structures and activity, and other factors related to the patient including status of the fellow eye, age, general health, and psychological status.…”
Section: Introductionmentioning
confidence: 99%
“…It can be performed through a trans-scleral approach (exoresection) or through an internal approach utilizing pars plana vitrectomy (endoresection). Endoresection surgery has been utilized over the last three decades with promising results, but only the advances in vitreoretinal surgery technology made in recent years have significantly improved the technique [16,17]. In recent years, endoresection of the tumor utilizing pars plana vitrectomy combined with adjuvant ruthenium brachytherapy has proven to be an effective treatment for selected patients with large choroidal melanoma [12,17,31].…”
Section: Introductionmentioning
confidence: 99%
“…This option has proven to preserve vision; however, it is associated with various complications such as failed vitreoretinal surgery (44–70%), ocular hypertension (21%), retinal detachment (21%), and submacular haemorrhage (16%) [ 38 , 39 , 42 ]. Transscleral resection has higher recurrence rates in contrast to brachytherapy [ 43 ]. Puusaari et al [ 44 ] found that the actuarial recurrence rate was 41% in the resection group vs. 7% in the brachytherapy group five years following intervention.…”
Section: Enucleationmentioning
confidence: 99%